Degradation rate of vitamin B6 on red chili pepper drying by blanching-brine-calcium pretreatment - Arifin, Uma Fadzilia; Djaeni, Mohamad (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2017)
Drying is one of the alternatives to prevent spoilage in red chili pepper by removing moisture content. Red chili pepper (Capsicum frutescens) has complex nutrition components such as vitamins and bioactive compound. However, vitamin B6 content in chili can degrade significantly in drying process by heat. This research studied degradation rate of vitamin B6 in chili drying process under various pretreatments and temperatures. In this study, post-harvest chili before dried was pretreated by blanching, osmotic dehydration with brine, immersing in calcium chloride solution and the combination of all them. They were dried in tray dyer at various temperatures 40°C, 50°C, 60°C and 70°C. Degradation of vitamin B6 content was analyzed every 2 hours by High-Performance Liquid Chromatography for 8 hours. Results showed that blanching-brine-calcium pretreatment was expected to reduce drying time and retain high content of vitamin B6 in red chili pepper. The degradation rate of vitamin B6 in chili followed second-order reaction. The degradation rate was influenced by temperature change referring to Arrhenius equation with activation energy was about 31.97 kJ/ mol K and constant rate (k0) was 3.769. Therefore, the vitamin B6 retention can be estimated at various pretreatments, times and temperatures. Furthermore, the favorable drying conditions can be evaluated.